Potential of pigeon pea as a trap crop for control of fruit worm infestation and damage to okra. (23rd July 2014) - Ratnadass, Alain; Zakari‐Moussa, Ousmane; Kadi‐Kadi, Hame A.; Kumar, Sanjeet; Grechi, Isabelle; Ryckewaert, Philippe; Salha, Halarou; Akourki, Moussa; Maâzou, Abdul A.; Siaka, Saïdou A.; Salami, Issoufou
Abstract The potential of perimeter trap cropping, using short and extra‐short duration pigeon pea (SD PP and ESD PP), sorghum and cotton, was evaluated in Niger as an agroecological alternative to pesticide application on okra for the management of the tomato fruit worm (TFW) Helicoverpa armigera (Hübner). In 2008, infestation by TFW and damage by fruit worms of unsprayed okra with SD PP borders was intermediate between cypermethrin‐sprayed and unsprayed pure okra crops. In 2009, the cypermethrin‐sprayed okra was significantly less damaged by fruit worms than in the unsprayed pure okra, as well as in the unsprayed okra crops with SD PP, sorghum and cotton borders. In 2010, the pure okra crop sprayed with cypermethrin was significantly less infested by TFW than the unsprayed pure okra crop and the unsprayed okra crop with SD PP borders. The unsprayed okra crop with ESD PP borders was intermediate between cypermethrin‐sprayed and unsprayed pure okra crops. The slightly lower TFW infestation of the unsprayed okra crop with ESD PP borders was a result of increased top‐down regulation by predator spiders, whose colonization was significantly higher on the unsprayed okra crop with ESD PP borders than on both (sprayed and unsprayed) pure okra crops.